A nomogram to predict unfavourable outcome in patients receiving oral anticoagulants for atrial fibrillation after stroke. (December 2020) - Cappellari, Manuel; Seiffge, David J; Koga, Masatoshi; Paciaroni, Maurizio; Forlivesi, Stefano; Turcato, Gianni; Bovi, Paolo; Yoshimura, Sohei; Tanaka, Kanta; Shiozawa, Masayuki; Yoshimoto, Takeshi; Miwa, Kaori; et al.
Introduction: It is unknown whether the type of treatment (direct oral anticoagulant versus vitamin K antagonist) and the time of treatment introduction (early versus late) may affect the functional outcome in stroke patients with atrial fibrillation. We aimed to develop and validate a nomogram model including direct oral anticoagulant/vitamin K antagonist and early/late oral anticoagulant introduction for predicting the probability of unfavourable outcome after stroke in atrial fibrillation-patients. Patients and Methods: We conducted an individual patient data analysis of four prospective studies. Unfavourable functional outcome was defined as three-month modified Rankin Scale score 3 -6. To generate the nomogram, five independent predictors including age (<65 years, reference; 65--79; or 80), National Institutes of Health Stroke Scale score (0--5 points, reference; 6--15; 16--25; or >25), acute revascularisation treatments (yes, reference, or no), direct oral anticoagulant (reference) or vitamin K antagonist, and early (7 days, reference) or late (8--30) anticoagulant introduction entered into a final logistic regression model. The discriminative performance of the model was assessed by using the area under the receiver operating characteristic curve. Results: A total of 2102 patients with complete data for generating the nomogram was randomly dichotomised into training ( n  = 1553) and test ( n  = 549) sets. The area under the receiver operating characteristic curve was 0.822 (95% confidence interval, CI: 0.800--0.844) in the training set and 0.803 (95% CI: 0.764--0.842) in the test set. The model was adequately calibrated (9.852; p  = 0.276 for the Hosmer--Lemeshow test). Discussion and Conclusion: Our nomogram is the first model including type of oral anticoagulant and time of treatment introduction to predict the probability of three-month unfavourable outcome in a large multicentre cohort of stroke patients with atrial fibrillation.